Calydorea minuana, a new species of Iridaceae from Río de La Plata Grasslands, South America - Deble, Leonardo Paz; Alves, Fabiano Da Silva; Oliveira-Deble, Anabela S. De (Phytotaxa, 2016)
A new species of Calydorea is described and illustrated for northern Uruguay and southwest Rio Grande do Sul State, Brazil. This new species is closely related to C. nuda however, differs by its dark-blue or dark violet-blue flowers, stamens with white-cream filaments and bigger anthers, and style branches free towards the top. Data on phenology, geographic distribution, conservation, and habitat are provided. Moreover, a table to segregate this new species from its related species, and an identification key for the Calydorea species occurring in the sub-region of “Northern Campos” of Río de La Plata Grasslands are supplied.